(untitled) (Contemporary Journal of Social Science Review, 2025)
A Language becomes more powerful when it is understood not only by the closest people, but by a wider community; thus, it is not only a constituent of communication, but also an integral aspect of identity. Multilingualism serves multiple benefits, as it enhances cognitive skills, promotes cultural awareness, adds academic and educational value, and helps appreciate both local and foreign languages. The study explores the impact of multilingualism that goes beyond the ability to communicate in multiple languages. The goal of this research is to promote multilingualism and social cohesiveness by emphasizing the value of all extra languages, including majority, minority, and regional languages. This research supports Mansoor’s (2004) proposed type of education that promotes cultural pluralism and minority languages in Pakistan. The research design integrates both qualitative and quantitative data to provide a more comprehensive understanding. Lecturers and undergraduate Students from the university participated in this research. The research was carried out on a microscale level. The findings refute the assumptions that exposure to more than one language hinders cognitive growth. Most of the interviewees either opposed or were not sure about this idea. On the other hand, many responders and interview revelations noted multilingualism as a mind stimulant.